Implementasi Sistem Informasi Manajemen Persediaan Bahan Baku Menggunakan Metode EOQ, ROP, Dan Safety Stock Pada Alfa Bakery - Triase; Fathiya Hasyifah Sibarani; Panjaitan, Mira Aripin (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Rapid technological advances have increased efficiency in processing and utilizing information, especially in the business sector. One important application of technology is management information systems, especially in raw material inventory management. This inventory is a key element in inventory management which greatly influences the smooth production process. Alfa Bakery, which was founded in 2022, faces difficulties in managing supplies of raw materials that have a limited shelf life, which has the potential to cause waste and financial losses. This research aims to design a raw material inventory management information system using the Economic Order Quantity (EOQ), Reorder Point (ROP) and Safety Stock methods. It is hoped that by implementing this method, Alfa Bakery can better manage stock, reduce waste and increase production efficiency.